Drainage basin committee report for the Hudson Bay basins - United States. Water Resources Committee. (Washington, D.C. : U.S. G.P.O., 1937)
"December 1937." Cover title. 51. Souris River-Devils Lake -- 52. Red River of the North -- 53. Rainy River. Mode of access: Internet.